The Insula Is a Hub for Functional Brain Network in Patients With Anti-N-Methyl-D-Aspartate Receptor Encephalitis - Li, Chunyan; Pang, Xiaomin; Shi, Ke; Long, Qijia; Liu, Jinping; Zheng, Jinou (Frontiers in Neuroscience, 2021)
Background: With the development of imaging analyses, more attention has been focused on the characteristic structural and functional imaging patterns in patients with autoimmune encephalitis. However, the neural bases and cognitive impairment in Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis are unclear. Our study aimed to identify the alterations in brain functional network in patients with anti-NMDAR encephalitis and whether these alterations contributed to cognition and mood disorders. Methods: Twenty-one patients and twenty-one gender, age and education-matched healthy controls underwent resting-state fMRI scans and neuropsychological tests（including Montreal Cognitive Assessment (MoCA), Hamilton Anxiety Scale (HAMA), Hamilton Depression Scale(HAMD24)）.First, functional magnetic resonance imaging (fMRI) was used to construct functional brain networks, and Graph theory was used to identify topological parameters of the networks. Next, We extracted the aberrant topological organization of the function network as seeds compared causal connectivity with the whole brain. Also, we explored their correlations with deficits in cognitive performance. Results: Relative to healthy controls, lower MoCA scores and higher HAMA and HAMD24 scores in anti-NMDAR encephalitis patients were detected (P < 0.05). The nodal clustering coefficient and nodal local efficiency of Insula_L in anti-NMDAR encephalitis patients were significantly decreased. (P< 0.05, Bonferroni correction). Compared to healthy controls, anti-NMDAR encephalitis patients showed weakened causal connectivity of the left Insula with the Parietal_Inf_L. The Parietal_sup_L exhibited enhanced causal connectivity with the left Insula compared to controls. Unexpectedly, these alterations were no found to be associated with neuropsychological tests scores. Conclusions: This study emphasizes that the topological attribute abnormality of the brain function network of patients with anti-NMDAR encephalitis and the related effective connection abnormality may be involved in the process of cognitive and emotional disorders. These results will help to understand the structure and function of the brain network of the disease and further explore the neuropathophysiological mechanism.